Synthesis of palm kernel oil alkanolamide using lipase - Abdul Rahman, M.B.; Yap, C.L.; Dzulkefly, K.; Abdul Rahman, R.N.Z. (2003)
Fatty monoethanolamides were synthesized in organic solvent from palm kernel olein (PKL) and palm kernel stearin (PKS) using a lipase from Candida rugosa. The transamidation reactions of PKL and PKS were enhanced in the presence of lipase. The optimal yield was achieved at reaction time 72 hours for both systems with PKL and PKS as the substrates. For PKL as the substrates, the optimal reaction temperature was 40°C, whereas with PKS as the substrate, no optimum temperature was found (in the range of temperature studied) where the relative yield increased with the increasing temperature. Lipase functioned better in hydrophobic solvents compared to hydrophilic solvents. The best solvent for the reactions was isooctane. Increasing the amount of the monoethanolamine used resulted in the increasing solubility of the reactants and products, hence, increasing the yield of the product. For PKL, increasing the mole ratio of PKL:monoethanolamine from 1:1 to 1:15 increased the relative yield to 4.5 fold. However, for PKS, the increase was only 2.5 fold. The optimal ratio of enzyme/PKL (or PKS) was 0.035. In the water activity studies, the preequilibrium and the direct salt hydrate addition methods were used. Generally, PKL always showed the higher relative yield compared to PKS. At the optimum condition at room temperature, the yield of PKL monoethanolamide was 77.0% and the yield of PKS monoethanolamide was 39.0%. Kinetic studies also showed a clear preference to PKL in which its Km value was 10-fold lower than that of PKS at room temperature. © 2003, Japan Oil Chemists' Society. All rights reserved.